1995
DOI: 10.1139/b95-116
|View full text |Cite
|
Sign up to set email alerts
|

Growth response ofFestuca altaica,Festuca hallii, andFestuca campestristo temperature

Abstract: In Alberta, the rough fescue complex consists of Fesruca alraica Trin., Fesrlcca hallii (Vasey) Piper, and Fesruca carr~pesrris Rydb. The potential commercial value of these species for grazing, and their ecological significance, necessitates an increased understanding of their environmental adaptation. This study compared the growth response of the three species at five temperature regimes of 7: 3, 12:8, 17:13, 22: 18, and 27:23"C (1ight:dark; 18-h photoperiod). Seedlings were established and grew for 10 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…Other cooltemperate grass species have been reported to respond sitnilarly (e.g. Fe.stuca species; King, Hill & Willms 1995). The tetnperature tesponse in the present experitnent is more negative, but this could be anticipated in view of the hot weather conditions which preceded the tneasutement period (a daily maximum of 7, of on average 37-2 °C).…”
Section: Discussionmentioning
confidence: 54%
“…Other cooltemperate grass species have been reported to respond sitnilarly (e.g. Fe.stuca species; King, Hill & Willms 1995). The tetnperature tesponse in the present experitnent is more negative, but this could be anticipated in view of the hot weather conditions which preceded the tneasutement period (a daily maximum of 7, of on average 37-2 °C).…”
Section: Discussionmentioning
confidence: 54%
“…Notably, the decline in accumulated herbage with warming was largely due to graminoids rather than forbs. King et al (1995) also showed that decreases in growth of three Festuca species were due to increased temperature and not changes in soil moisture. That study suggested that this was an adaptation to limit growth to periods of lower temperatures, thus restricting growth to early in the growing season when soil moisture is high.…”
Section: Discussionmentioning
confidence: 89%
“…There is also evidence that productivity at northern latitudes is increasing due to climate change, although this trend is inconsistent across North America (Zhou et al, 2001). Warming can have negative effects on biomass, however, if plants are optimally adapted to their current (i.e., lower) temperature (King et al, 1995; Bertrand et al, 2008). The response of plant biomass to warming has also been shown to depend on other environmental variables, such as precipitation availability (Hoeppner and Dukes, 2012).…”
mentioning
confidence: 99%
“…High root‐to‐shoot ratio is an important mechanism in plant adaptation to environmental stresses (King et al, 1995). Higher root‐to‐shoot biomass ratio in heat‐tolerant than in heat‐sensitive cultivars has been reported in various species, including Kentucky bluegrass (Bonos et al, 1995); potato ( Solanum tuberosum ) (Basu and Minhas, 1991); and wheat ( Triticum aestivum ) (Mann et al, 1994).…”
Section: Discussionmentioning
confidence: 99%